How Inheritance Expectations Impact Household Savings - Ignacio Belloc; José Alberto Molina (Institute of Labor Economics (IZA), 2025)
This paper examines how expecting to receive an inheritance impacts household savings decisions. Life-cycle consumption models indicate that the expectation of inheriting should reduce current savings plans for forward-thinking consumers. We investigate how inheritance expectations shape savings behavior within the household, considering factors such as liquidity constraints and education. To do so, we use household fixed effects to account for time-invariant factors and exploit within-household variation over time by using panel data from the Japanese Panel Survey of Consumers (2003-2019), which provides individual-level information and overcomes endogeneity concerns commonly present in cross-sectional studies. Our findings reveal that households adjust their current savings in anticipation of receiving future inheritances. Specifically, men decrease their current savings by an average of 5.4 percent if they expect to receive an inheritance in the future. Additionally, we find more pronounced changes in savings among households with higher levels of education and incomes, which are less likely to face liquidity constraints. These findings inform inheritance fiscal policies, such as inheritance taxes, revealing that households consider the expectation of inheriting in the future for current saving decisions.
Keywords: D14; D15; D84; 330; intra-household allocation; savings; inheritance expectations; panel data; JPSC